PENGEMBANGAN READING SUPPLEMENTARY MATERIAL SEBAGAI UPAYA MENANGKAL RADIKALISME - Andriyani, Santi; Yulistianti, Hayu Dian; Sai’dah, Nusrotus (English Department FBS UNP, 2019)
The practice of radicalism in Indonesia has spread to all society, including young people. This study is aimed at developing reading book that contains various types of English-language texts with Aswaja values. This research is an R & D research by adopting the Borg & Gall stages, namely: Needs analysis, Planning, Reading the complementary material design, expert assessment review, revision, product trials and user ratings, data revision and analysis, and final products. The subjects of this study were 48 students from both class X and class XI by taking a random sample. The results of this study showed that: the score from expert judgment was good with an average of 4; the result of product trial by using the t-test independent sample t-test as a test for the implementation of supplementary reading material showed that there were differences between the experimental class and the control class with a sig value of 0.00.